Surgical Treatment and Outcome of Giant Intracranial Aneurysm in KCMH from 2005 - 2010 - Sriamornrattanakul, Kitiporn; Chantra, Kraisri; Khaoroptham, Surachai (Thai Journal of Neurological Surgery, 2025)